Time to Resolution of Microscopic Hematuria after Robotic Radical Prostatectomy. Issue 5 (September 2019) - Hertz, Alexandria M.; Janssen, Karmon M.; George, Evalyn I.; Brand, Timothy C.
Abstract: Introduction: We established a timeline for the resolution of microscopic hematuria after robotic radical prostatectomy and related diagnoses after surgery. Methods: A retrospective chart review of all patients who underwent robotic radical prostatectomy from January 1, 2010 to December 31, 2015 was performed. A total of 185 patients were included in the study. Demographics and all postoperative urinalyses were reviewed. Mean number of red blood cells since prostatectomy was plotted over time and statistical analyses were performed using SPSS® statistics software. Results: Average patient age was 61 years (range 34 to 80) and median Gleason score was 3+4=7. Of the 185 patients 52 (28%) had a smoking history and 32 (17%) received radiation therapy. Median followup was 50 months. Evaluation of the average number of red blood cells since prostatectomy demonstrated a significant difference between months 0 and 3 (p <0.001), with resolution of microscopic hematuria during that time. The average number of red blood cells during the remainder of followup was 3. Overall 57 patients underwent evaluation for microscopic hematuria. Malignancies were identified in 2 patients, with urothelial carcinoma of the bladder in 1 and renal cell carcinoma of the kidney in the other. Neither patient had a history of smoking or radiation. A large number of evaluations were negative (23 of 57). The remainder demonstrated nephrolithiasis, bladder neck contracture, cystitis, disease progression, ureteropelvic junction stricture and urachal remnant. Conclusions: Microscopic hematuria following robotic radical prostatectomy should resolve within 3 months of surgery. After this time microhematuria should be considered clinically significant and should be evaluated accordingly, although many of the evaluations may be benign.